To the problem of the pragmatic equivalence in translation - N V Karpovskaya (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2011)
The article is dedicated to the investigation of the influence of the language units pragmatic potential on the process of taking translation decisions. The most part of attention is focused on the notion of the pragmatic equivalence, on the translation difficulties of the lingual pragmatic categories components, as well as on the specifics of the pragmatic relations in the process of bilingual communication.